Explicit Modeling of Radon‐222 in HydroGeoSphere During Steady State and Dynamic Transient Storage. Issue 1 (19th December 2018) - Gilfedder, B.S.; Cartwright, I.; Hofmann, H.; Frei, S.
Abstract: Transient storage zones (TSZs) are located at the interface of rivers and their abutting aquifers and play an important role in hydrological and biogeochemical functioning of rivers. The natural radioactive tracer 222 Rn is a particularly well‐suited tracer for studying TSZ water exchange and age. Although 222 Rn measurement techniques have developed rapidly, there has been less progress in modeling 222 Rn activities. Here, we combine field measurements with the numerical model HydroGeoSphere (HGS) to simulate 222 Rn emanation, decay and transport during steady state (riffle‐pool sequence) and transient (bank storage) conditions. Comparing the HGS mean water ages with the conventional 222 Rn apparent ages during steady state showed a systemic underestimation of apparent age with increasing dispersion and especially where large concentration gradients exist within the subsurface. A large underestimation of apparent water age was also observed at the advective front during bank storage where regional high 222 Rn groundwater mixes with newly infiltrated surface water. The explicit modeling of radiogenic tracers such as 222 Rn offers a physical interpretation of this data as well as a useful way to test simplified apparent age models. Abstract : Article impact statement : This work couples a physically based model (HydroGeoSphere) with radon measurements to understand water ages in transient storage zones during steady and nonsteady states.